Methods Of Teaching Russian Language In National Groups In Uzbekistan (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article examines various issues of teaching Russian language to foreigners from the standpoint of a communicative-activity approach, with a special place given to the importance of vocabulary learning. This paper also examines the motivational aspect in the study of Russian as a foreign language as the basis for its high-quality mastery